Cell Phones in the Neonatal Intensive Care Unit: How to Eliminate Unwanted Germs. (December 2016) - Kirkby, Sharon; Biggs, Christine
Abstract : Background: Infants admitted to the neonatal intensive care unit (NICU) are more susceptible to infections due to immature immune systems or invasive procedures that compromise protection from bacteria. These infants may stay in the NICU for extended periods of time, are exposed to many caregivers, and may be exposed to other infections. Cell phone use by both family and staff introduce unwanted bacteria into the NICU environment, thereby becoming a threat to this high-risk population. Purpose: A quality improvement initiative to evaluate and improve the cleanliness of cell phones used in the NICU. Methods: A convenience sample of 18 NICU parents and staff. The participants' cell phones were sampled for bacteria pre- and postcleaning with disinfectant wipes and sent to the microbiology laboratory for a 2-day incubation period. In addition, each participant completed a survey on cell phone cleaning habits. Results: Microbial surface contamination was evident on every phone tested before disinfecting. All phones were substantially less contaminated after disinfection. Implications for Practice: A standardized cleaning process with a surface disinfectant reduced the amount of germs and potential transmission of nosocomial pathogens within the NICU. The simple exercise illustrated the importance of cell phone hygiene in a high-risk population. The implementation of a simple cleaning process has been an easy and effective way to rid unwanted organisms from this high-risk population. Implications for Research: Further research evaluating transmission of nosocomial infections from cell phones would enhance the evidence to establish hospital policies on cleaning devices.